Literatur Riview :Efektivitas Penggunaan Alat Pelindung Diri (APD) dalam Menurunkan Risiko Kecelakaan Kerja - Andwina Andwina; Susilawati Susilawati; Rahmah Dwi Asti; Nurul Zahra (Lembaga Pengembangan Kinerja Dosen, 2026)
Workplace accidents are a major issue in the industrial world, placing significant emphasis on worker safety and health. One preventive measure that has proven effective in reducing workplace accident rates is the use of personal protective equipment (PPE). This study aims to evaluate the effectiveness of PPE in reducing the risk of workplace accidents in high-risk work environments. The methodology employed includes a literature review of previous studies and direct observations in the manufacturing and construction industries. The findings indicate that consistent and standardized use of PPE can reduce workplace accident rates by 60–80%, depending on the industry type and the level of employee compliance with established safety standards. In addition, the study highlights that the effectiveness of PPE is strongly influenced by factors such as worker awareness, company safety policies, training programs, and supervisory enforcement. Lack of compliance or improper use of PPE remains a challenge in many workplaces, often caused by discomfort, limited knowledge, or negligence. Therefore, the implementation of continuous safety training, monitoring systems, and strict enforcement of safety regulations is essential to ensure proper PPE usage. Overall, this study emphasizes that while PPE alone cannot eliminate workplace accidents, it plays a critical role as part of an integrated occupational safety strategy. The findings suggest that industries should prioritize investment in PPE quality, worker education, and safety culture development to create safer and healthier work environments.